Effects of Whole-Body Vibration Therapy on Body Functions and Structures, Activity, and Participation Poststroke: A Systematic Review. Issue 9 (1st September 2014) - Liao, Lin-Rong; Huang, Meizhen; Lam, Freddy M.H.; Pang, Marco Y.C.
Abstract : Background: Whole-body vibration (WBV) has gained increasing popularity in rehabilitation. Recent studies have investigated the application of WBV in individuals with chronic illnesses, including stroke. Purpose: The purpose of this study was to compare WBV exercise with the same exercise condition without WBV and with other types of physical exercise in enhancing body functions and structures, activity, and participation in individuals with stroke and examine its safety. Data Source: Electronic searches were conducted on MEDLINE, CINAHL, PEDro, PubMed, PsycINFO, and Science Citation Index. Study Selection: Randomized controlled trials (RCTs) that investigated the effects of WBV among individuals with stroke were identified by 2 independent researchers. Ten articles (9 studies, totaling 333 study participants) satisfied the selection criteria and were included in this review. Data Extraction: The methodological quality was rated using the PEDro scale. The results were extracted by 2 independent researchers and confirmed with the principal investigator. Data Synthesis: Only 2 RCTs were considered as demonstrating level 1 evidence (PEDro score ≥6 and sample size >50). Two RCTs examined the effects of a single WBV session, and 7 RCTs examined the effects of WBV programs spanning 3 to 12 weeks. No consistent benefits on bone turnover, leg motor function, balance, mobility, sensation, fall rate, activities of daily living, or societal participation were found, regardless of the nature of the comparison group. Adverse events were minor. Limitations: A broad approach was used, with stroke as an inclusion criterion for review. No solid evidence was found concerning the effects of WBV on subgroups of people with specific stroke-related deficits due to the heterogeneity of patient groups. Conclusions: Based on the review, there is insufficient evidence to support clinical use of WBV in enhancing body functions and structures, activity, and participation after stroke.